Alan Bennett at the BBC - Frears, Stephen; Mowbray, Malcolm; Foster, Giles; Schlesinger, John; Bennett, Alan; Henman, Ray; Tufano, Brian; Crosby, Nat; Routledge, Patricia; Bates, Alan; Day-Lewis, Daniel (BBC Worldwide, 2009)
This outstanding four-disc box set contains much of Bennett's finest work, ranging in settings from Morecambe to Moscow and is testimony to his acute ear, sharp eye and generous mind and his belief in the old Yorkshire adage that "there's nowt so queer as folk". The dozen items include the first of his "Talking Heads" series (Patricia Routledge as "A Woman of No Importance"), and dramatic portraits of Kafka (Daniel Day-Lewis) and Proust (Alan Bates). Looking as good on the big screen as on the box, the films blur the line between TV and cinema and perhaps the best thing in this collection is the pair of films written nearly 20 years apart known as "Single Spies": Alan Bates as the exiled Guy Burgess meeting Coral Browne in the USSR in "An Englishman Abroad" and James Fox as Anthony Blunt discussing art with HMQ (Prunella Scales) in "A Question of Attribution". Both are directed by John Schlesinger. [www.guardian.co.uk]